Distributional issues in the context of the economic crisis in Europe - Andrew Watt (Intereconomics, 2009)
This article takes a step back from the debate on the precise causes of the crisis and the detailed steps needed to resolve it. It focuses on distributional issues and discusses the ways in which widening income inequality in most European countries has been linked to factors that lie behind the crisis. It then considers distributional effects of current efforts to resolve the crisis and explains why crisis-resolution policies need to address distributional concerns. Finally it proposes measures, many of which require coordination at least at the European level, to address the distributional crisis that otherwise awaits us in coming years and that will ultimately help to establish a new, more economically and socially balanced growth model.
Keywords: 330